THE PRINCIPAL'S LEADERSHIP STYLE AS ORGANIZATIONAL CULTURE IN IMPROVING TEACHER PERFORMANCE IN CHANGING STUDENT CHARACTER AT SDN KUTA RENTANG ACEH BESAR - Akmaluddin; Siti Mayang Sari; Aidi Husni (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
This research uses a qualitative descriptive method with a case study type of research which produces a picture of increasing optimal teacher performance and is influenced by the school principal's leadership style and positive organizational culture in terms of several phenomena that exist in the school. A positive organizational culture supports the creation of a good work environment so that it can optimize teacher performance. A positive organizational culture supports the creation of a good work environment so that it can optimize teacher performance. Openness and effective communication, collaboration and cooperation, self-development, discipline and responsibility as well as respect or appreciation can improve teacher performance and leaders' goals in organizing individuals into schools. This research was carried out at SDN Kuta Rentang Aceh Besar. This research aims to determine the increase in teacher performance based on the principal's leadership an organizational culture and optimizing teacher performance in changing student character. The leadership used by the school principal can provide an increase in teacher performance and the development of teacher organizational culture in the school. Because a leader's democratic leadership style is a benchmark for organizational culture and can involve teachers in participating in making decisions to improve teacher performance professionally and efforts to change student character